Filsafat Pancasila dalam Budaya Gotong Royong (Pengiri) Masyarakat Dayak Mali - Urbanus, Rohit; Utomo, F.X. Kurniawan Dwi Madyo (Sekolah Tinggi Agama Katolik Negeri Pontianak, 2022)
Pancasila is a part of philosophical system. Essentially, humans are placed as the main subject and as the basis for understanding all reality. Gotong royong is the essence of Pancasila. One of the gotong royong culture is the culture of the Dayak Mali community. Pancasila and the culture of envy are the character of the Indonesian nation. The writing of this study is focused on the value of gotong royong as part of the Pancasila philosophy in the culture of the Dayak Mali community. The method used in this paper is a qualitative method in the form of a literacy study in elaborating the value of gotong royong contained in Pancasila with the culture of envy. Malian Dayak culture is often identified with dances, symbols, tattoos, and so on. Literatures related to the Malian Dayak culture are also still few, not many writers have studied the existing cultures. Therefore, this paper aims to explore the meaning of gotong royong in the Malian Dayak culture as well as to dissect the philosophical meanings in it. The results of this study are Pancasila Philosophy which is described as a theoretical framework used to dissect the value of gotong royong contained in the Pengiri culture. The Malian Dayak people practice this culture from generation to generation. The Malian Dayak community is obliged to preserve this Pengiri culture. Culture is an integral part of the life of the Indonesian nation. The spirit of gotong royong is the unique spirit of the Indonesian people. Therefore, the culture of gotong royong (pengiri) is an asset of the Indonesian nation that needs to be maintained and developed.